Defect-induced magnetism in TiO2: An example of quasi 2D magnetic order with perpendicular anisotropy - Stiller, Markus; Esquinazi, Pablo D. (Frontiers in Physics, 2023)
Magnetic order at room temperature induced by atomic lattice defects, like vacancies, interstitials or pairs of them, has been observed in a large number of different nonmagnetic hosts, such as pure graphite, oxides and silicon-based materials. High Curie temperatures and time independent magnetic response at room temperature indicate the extraordinary robustness of this new phenomenon in solid state magnetism. In this work, we review experimental and theoretical results in pure TiO$_2$ (anatase), which magnetic order can be triggered by low-energy ion irradiation. In particular, we discuss the systematic observation of an ultrathin magnetic layer with perpendicular magnetic anisotropy at the surface of this oxide.